Tangible user interfaces for learning. (23rd January 2013) - Markova, Milena S.; Wilson, Stephanie; Stumpf, Simone
Tangible User Interfaces (TUIs), systems characterised by the embodiment of interaction in physical objects, have attracted general interest but have not yet been widely adopted for learning. Employing these kinds of novel technologies could yield substantial benefits to learners. This paper provides a review of state-of-the-art TUIs for learning, scoped by a revised definition of TUIs that serves to delineate and differentiate these from other kinds of interfaces. We propose a classification framework that attends to important aspects of TUIs for use in learning and review tangible systems within this classification to expose research and design gaps. Our work provides guidance for researchers and learning technologists to help identify potential research directions for TUIs for learning.